Effects of chronic beta-blocker treatment on admission haemodynamics in STEMI patients treated with primary angioplasty. Issue 5 (August 2020) - Roolvink, Vincent; Hemradj, Veemal V; Ottervanger, Jan Paul; van 't Hof, Arnoud WJ; Dambrink, Jan-Henk E; Gosselink, AT Marcel; Kedhi, Elvin; Suryapranata, Harry; ,
Background: The association between chronic beta-blocker treatment and haemodynamics at admission in patients with ST-segment elevation myocardial infarction treated by primary percutaneous coronary intervention is not well studied. We investigated the impact of chronic beta-blocker treatment on the risk of cardiogenic shock and pre-shock at admission in patients with ST-segment elevation myocardial infarction treated by primary percutaneous coronary intervention. Methods and results: A total of 4907 patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention were included in the study. A total of 1148 patients (23.3%) were on chronic beta-blocker treatment. Cardiogenic shock was observed in 264 patients (5.3%). Pre-shock was defined as a shock index (the ratio of heart rate and systolic blood pressure) of 0.7 or greater, and was observed in 1022 patients (20.8%). The risk of cardiogenic shock in patients with chronic beta-blocker treatment was not increased (adjusted hazard ratio (HR) 0.97, 95% confidence interval (CI) 0.65–1.46, P =0.90). Chronic beta-blocker treatment was also not associated with an increased risk of pre-shock (adjusted HR 0.86, 95% CI 0.68–1.07, P =0.19). Also after propensity score matched analysis, there was no increased risk of cardiogenic shock or pre-shock in patients with chronic beta-blocker treatment (respectively HR 0.97, 95% CI 0.61–1.51, P =0.88 and HR 0.82, 95% CI 0.65–1.06, P =0.12). Conclusion: In ST-segment elevation myocardial infarction, chronic beta-blocker treatment is not associated with an increased risk of cardiogenic shock or pre-shock.